Perturbing DDR signaling enhances cytotoxic effects of local oncolytic virotherapy and modulates the immune environment in glioma - Koch, Marilin; Zdioruk, Mykola; Nowicki, Michal O.; Griffith, Alec M.; Aguilar-Cordova, Estuardo; Aguilar, Laura K.; Guzik, Brian W.; Barone, Francesca; Tak, Paul Peter; Schregel, Katharina; Hoetker, Michael S.; Lederer, James A.; et al. (Molecular therapy. Oncolytics, 2022)
CAN-2409 is a replication-deficient adenovirus encoding herpes simplex virus (HSV) thymidine kinase (tk) currently in clinical trials for treatment of glioblastoma. The expression of tk in transduced cancer cells results in conversion of the pro-drug ganciclovir into a toxic metabolite causing DNA damage, inducing immunogenic cell death and immune activation. We hypothesize that CAN-2409 combined with DNA-damage-response inhibitors could amplify tumor cell death, resulting in an improved response. We investigated the effects of ATR inhibitor AZD6738 in combination with CAN-2409 in vitro using cytotoxicity, cytokine, and fluorescence-activated cell sorting (FACS) assays in glioma cell lines and in vivo with an orthotopic syngeneic murine glioma model. Tumor immune infiltrates were analyzed by cytometry by time of flight (CyTOF). In vitro, we observed a significant increase in the DNA-damage marker γH2AX and decreased expression of PD-L1, pro-tumorigenic cytokines (interleukin-1β [IL-1β], IL-4), and ligand NKG2D after combination treatment compared with monotherapy or control. In vivo, long-term survival was increased after combination treatment (66.7%) compared with CAN-2409 (50%) and control. In a tumor re-challenge, long-term immunity after combination treatment was not improved. Our results suggest that ATR inhibition could amplify CAN-2409’s efficacy in glioblastoma through increased DNA damage while having complex immunological ramifications, warranting further studies to determine the ideal conditions for maximized therapeutic benefit.
Online verfügbar 31 July 2022, Version des Artikels 12 August 2022
Gesehen am 13.03.2023